Protective effect of Honokiol against endometriosis in Rats via attenuating Survivin and Bcl-2: A mechanistic study - Wang, Y; Jiang, L-L; Wu, J-F; Liu, Z (Cellular and Molecular Biology, 2016)
Nearly 10-15% of women in the reproductive age were affected by endometriosis and currently facing the unmet need of effective therapeutic interventions for its management. Concerning this, the present study was intended to investigate the effect of Honokiol (HK) for the treatment of endometrial hyperplasia. The rat endometrial model was established and subsequently administered with a numerous dose of HK. The histopathology of tissues was also investigated. Results showed that, HK effectively inhibit the proliferation of rat edometeriotic tissues in a dose dependent manner. In terminal deoxynucleotidyl transferase (TdT) -mediated dUTP biotin nick end labeling (TUNEL) method, HK was able to bring apoptosis in endometrotic cells. Moreover, it also inhibits the mRNA levels of Survivin gene and Bcl-2 (B-cell lymphoma 2) in qPCR and Western blot analysis together with increases the mRNA level of apoptosis promoting factor Bax. These results clearly suggest that, HK was proficient to provoke apoptosis of rat endometriotic cells.